Diversity of bats at the forest edge of two golf courses in Sarawak, Borneo - Lim, Yang Ping (Universiti Malaysia Sarawak (UNIMAS), 2012)
A total of six sampling nights was conducted in each of two selected golf courses, which were Sarawak Club Golf Resort and Damai Golf and Country Club to determine and compare the bat diversity. Twenty mist nets and two harp traps were set up in the forest edges of golf courses from March 15th - 18th 2011 in Sarawak Club Golf Resort and March 22th - 25th , 2011 in Damai Golf and Country Club. Sampling was conducted again at both study sites from February 8th - 11th , 2012 in Damai Golf and Country Club and February 14th - 17th , 2012 in Sarawak Club Golf Resort. A total of three bat species with 126 individuals were captured in Damai Golf and Country Club and three bats species with 34 individuals were captured in Sarawak Golf Course Resort. Species recorded from Sarawak Golf Course Resort were Cynopterus brachyotis, Balionycteris maculata and Tylonycteris pachypus while species recorded from Damai Golf and Country Club were Cynopterus brachyotis, Hipposideros galeritus and Hipposideros cervinus. The highest capture rate from both sampling sites was Cynopterus brachyotis. Statistical analyses used were Simpson Index, Shannon Index, Zar t-test, and Chi-square test. Bat species diversity for both sampling sites is low and there is no significant difference in bat diversity between Sarawak Golf Course Resort and Damai Golf and Country Club. It is suggested that golf course is not a suitable habitat for bats in Kuching and Samarahan Divisions.